Drag study of the nacelles of a tidal stream device using CFD - Martinez, Fabien (Cranfield University, 2010)
Nowadays, renewable energy is in full growth. In particular, offshore wind farms will be at the centre of UK energetic strategy in the coming years. However, other types of marine renewable are still at an early development stage. That is the case for tidal energy. Many projects have been undertaken but there is no candidate for competitive commercial applications yet. Deltastream is one of these numerous pioneering projects. It consists of a set of three marine current turbines mounted on a triangular base put down onto the seabed. The device is not moored and no harm is done to the environment. However, that makes the structure more sensitive to water flows. And it is important to ensure that it will remain at its location and not being carried along with the tidal streams. Using CFD, the present study aims to evaluate the drag on the nacelles of the structure and come up with solutions to reduce it as much as possible.
Keywords: Renewable energy; fluid dynamics; Deltastream; marine current turbine; tidal energy